Legal Aspects of Electronic Signatures In Indonesia - Rizky Amalia Dewi; Budi Santoso (Eduvest - Journal of Universal Studies, 2022)
Study this aim for research and analyze aspect law sign hand electronic based on perspective law positive in Indonesia. Study this use method study juridical normative, with using secondary data, research conducted with use studies bibliography. Approach analysis used is descriptive analytical. Based on results study is known that sign hand electronics in essence is something sign agreement in form working electronics as form the agreement of the parties who make and carry out agreement electronics. Making sign hand electronic by agency sign hand specified electronics and mechanisms in regulation applicable legislation. Condition valid agreement electronic has determined in Article 53 paragraph 2 and Article 54 paragraph 1 and 2 of the Government Regulation concerning Organizer System and Transaction Electronic